Evaluation of Phytochemical and Anti-diarrheal Activity of Methanol Stembark Extract of Combretum hypopilinum Diels (Combretaceae) (Nigerian Journal of Pharmaceutical Research, 2021)
Introduction: The plant Combretum hypopilinum has many medicinal uses in Africa. Infusion of fresh or dry leaves are commonly taken as cholagogic, diuretic, and purgative and also to treat gastrointestinal disorders, including diarrhoea, dysentery, and stomach achesObjective: To carry out phytochemical and antidiarrheal studies on the methanol stembark extract of C. hypopilinum.Methods: The C. hypopilinum stembark (1kg) were extracted with methanol using cold maceration method for 9 days. The solvent was removed by rotary evaporator and the extract was partitioned with n-hexane, chloroform and ethyl acetate to give the n-hexane, chloroform, and ethyl acetate fractions respectively. The extract was subjected to preliminary phytochemical screening, acute toxicity study and antidiarrheal activity using animal models.Result: The following metabolites: carbohydrates, alkaloids, phenol, steroids, terpenes, saponins, flavonoids and tannins were revealed when the phytochemical screening of the plant extract was carried out. The oral median lethal dose (LD50) of crude extract in mice and rats was estimated to be above 5000 mg/kg. The antidiarrheal activity carried out at dose 150, 300 and 600 mg/bw i.p. using castor oil induced diarrheal, gastric-transit time and anti-enteropooling tests in mice and rats. The extract significantly (P
Keywords: Antidiarrheal; Combretum hypopilinum; Phytochemical constituents and Stembark